The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nano10010169
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanofibril/Carbon Nanomaterial Hybrid Aerogels for Adsorption Removal of Cationic and Anionic Organic Dyes

Abstract: Advances in nanoscale science and engineering are providing new opportunities to develop promising adsorbents for environmental remediation. Here, hybrid aerogels are assembled from cellulose nanofibrils (CNFs) and carbon nanomaterials to remove cationic dye methylene blue (MB) and anionic dye Congo red (CR) in single and binary systems. Two classes of carbon nanomaterials, carbon nanotubes (CNTs) and graphene nanoplates (GnPs), are incorporated into CNFs with various amounts, respectively. The adsorption, mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 55 publications
1
46
0
Order By: Relevance
“…In addition, Zare et al [ 22 ] studied the elimination of noxious Congo dye by MWCNTs from aquatic solutions and concluded that it has an excellent potential of 92%, with a q max of 352.10 mg g −1 of dye. Recently, Yu et al [ 23 ] used carbon nanocompounds for the removal of methylene blue and congo red dyes from aqueous solution. The maximum capacity of the adsorption process was found to be methylene blue and congo red at the levels of 1387.2 and 351.7 mg g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zare et al [ 22 ] studied the elimination of noxious Congo dye by MWCNTs from aquatic solutions and concluded that it has an excellent potential of 92%, with a q max of 352.10 mg g −1 of dye. Recently, Yu et al [ 23 ] used carbon nanocompounds for the removal of methylene blue and congo red dyes from aqueous solution. The maximum capacity of the adsorption process was found to be methylene blue and congo red at the levels of 1387.2 and 351.7 mg g −1 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 Dyes have been reported as one of the dangerous organic pollutants that require urgent attention because they are composed of many chemicals. 3 , 4 The major sources of dyes in water bodies are effluents from textile, paper, rubber, plastics, paints, printing, and leather industries. 5 , 6 The most commonly used dye in textiles and printing industries is methylene blue (MB).…”
Section: Introductionmentioning
confidence: 99%
“…Methylene blue functionalized-organic polymer 2740 [55] cellulose hydrogel 756 [56] modified grapheme oxide 257 [57] functionalized lignosulfate 63 [58] Methyl orange NiAlTi 1250 [59] MIL-101-NH 2 462 [60] polyaniline composite 148 [26] Crystal violet fly ash 433 [61] polyaniline-metal oxides 50 [24] Congo red MIL-100(Fe) 1791 [31] cellulose/carbon aerogels 585 [43] polyaniline-metal oxides 33 [24] Rhodamine B Ni-graphene composite 963 [14] MoS 2 nanoflowers 365 [62] polyaniline-metal oxides 20 [24]…”
Section: Discussionmentioning
confidence: 99%